The Role of Information Technology on Work Productivity - Sudrajat, Yayat (Journal of Management, 2023)
The goal of this research is to examine how information technology and communication effectiveness affect job satisfaction, how job satisfaction affects information technology and communication effectiveness on work productivity, how information technology affects work productivity, and how job satisfaction functions as a mediating variable in the relationship between information technology and work productivity and communication effectiveness and work productivity. Research of this kind is quantitative in nature. Eighty-four employees of PT Ciptaniaga Roda Berdikari served as the research sample. Method of statistical analysis with SPSS software. The findings of the study analysis indicate that job satisfaction cannot mediate the relationship between job satisfaction and the impact of information technology on work productivity, nor can job effectiveness mediate the relationship between job satisfaction and the impact of communication effectiveness on work productivity.